Воєнні реформи Івана IV Грозного - Іваненко, Владислав Вячеславович (Харків : Харківський національний університет імені В. Н. Каразіна, 2023)
Дипломна робота присвячена вивченню воєнних реформ Івана Грозного і їхнього впливу на розвиток Московської держави. Дослідження включало аналіз історичних джерел, документів та дослідницької літератури. Об’єктом розгляду є воєнні реформи Івана IV Грозного. Предмет роботи – особливості впровадження та характеристика воєнних реформ у період правління Івана Грозного. Метою роботи є дослідженні та характеристика воєнних реформ, проведених у період царювання Івана IV Грозного У першому розділі представлено огляд стану розвитку Московської держави на початку правління Івана Грозного та передумови до реформування. Другий розділ присвячений дослідженню цілей, завдань та суті воєнних реформ. В розділі третьому представлені підсумки реформування воєнної сфери та їх роль у подальшому розвитку держави. За результатами роботи, відповідно до поставлених завдань було здійснено висновки, що воєнні реформи Івана Грозного мали значний вплив на Московську державу. Вони сприяли зміцненню воєнної потужності та розвитку економіки. Однак, їхній негативний вплив на політичну сферу та свободу громадян не може бути знехтуваний. Дана робота розширює наше розуміння ролі воєнних реформ у пануванні Івана Грозного та допомагає краще оцінити їхній вплив на історичні події того періоду.

The thesis is devoted to the study of the military reforms of Ivan the Terrible and their impact on the development of the Moscow state. The research included the analysis of historical sources, documents and research literature. The object of consideration is the military reforms of Ivan IV the Terrible. The subject of the work is the peculiarities of the implementation and characteristics of military reforms during the reign of Ivan the Terrible. The purpose of the work is to study and characterize the military reforms carried out during the reign of Ivan IV the Terrible The first chapter presents an overview of the development of the Moscow state at the beginning of the reign of Ivan the Terrible and the prerequisites for reform. The second chapter is devoted to the study of the goals, tasks and essence of military reforms. The third chapter presents the results of the reform of the military sphere and their role in the further development of the state. According to the results of the work, in accordance with the tasks, it was concluded that the military reforms of Ivan the Terrible had a significant impact on the Muscovite state. They contributed to the strengthening of military power and the development of the economy. However, their negative impact on the political sphere and the freedom of citizens cannot be neglected. This work expands our understanding of the role of military reforms in the reign of Ivan the Terrible and helps to better assess their impact on the historical events of that period.
Military reforms of Ivan IV the Terrible
Керівник: Духопельников Володимир Михайлович, кандидат історичних наук, професор кафедри історії Східної Європи
Keywords: HUMANITIES and RELIGION::History and philosophy subjects::History subjects; Іван Грозний; воєнні реформи; стрілецьке військо; Укладення про службу; обрана тисяча; Ivan the Terrible; military reforms; rifle army; Agreement on service; chosen thousand